Spin-polarized lasing in manganese doped perovskite microcrystals - Penghao Li; Zhonghao Zhou; Guangliu Ran; Tongjin Zhang; Zhengjun Jiang; Haidi Liu; Wenkai Zhang; Yongli Yan; Jiannian Yao; Haiyun Dong; Yong Sheng Zhao (Nature Communications)
Abstract Spin-polarized lasers have demonstrated many superiorities over conventional lasers in both performance and functionalities. Hybrid organic-inorganic perovskites are emerging spintronic materials with great potential for advancing spin-polarized laser technology. However, the rapid carrier spin relaxation process in hybrid perovskites presents a major bottleneck for spin-polarized lasing. Here we report the identification and successful suppression of the spin relaxation mechanism in perovskites for the experimental realization of spin-polarized perovskite lasers. The electron-hole exchange interaction is identified as the decisive spin relaxation mechanism hindering the realization of spin-polarized lasing in perovskite microcrystals. An ion doping strategy is employed accordingly to introduce a new energy level in perovskites, which enables a long carrier spin lifetime by suppressing the electron-hole exchange interaction. As a result, spin-polarized lasing is achieved in the doped perovskite microcrystals. Moreover, the doped cation is a magnetic species allowing for the magnetic field control of the spin-polarized perovskite lasing. This work unlocks the potential of perovskites for spin-polarized lasers, providing guidance for the design of perovskites towards spintronic devices.